8th Georg Rajka International Symposium on Atopic Dermatitis: meeting report. (1st April 2015) - George, S.M.C.; Makrygeorgou, A.
Summary: The 8th Georg Rajka International Symposium on Atopic Dermatitis was held in Nottingham in May 2014. The 3‐day meeting featured a number of lectures by experts in the field of atopic dermatitis from around the world, as well as several original research presentations and a question and answer session. This paper aims to summarize the main oral presentations from the meeting, but is not meant to be a substitute for reading the conference proceedings and related references.